2015
DOI: 10.1055/s-0035-1549030
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Onset of Subdural Hematoma following Epidural Catheter Breakage

Abstract: Study Design Case report. Objectives To describe a case of delayed-onset spinal hematoma following the breakage of a spinal epidural catheter. Methods The authors describe the clinical case review. Results A 64-year-old woman had undergone epidural anesthesia 18 years before she was referred to our hospital because of lower-back pain and lower neurologic deficit with leg pain. The clinical examination showed the presence of a fragment of an epidural catheter in the thoracolumbar canal, as assessed by computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
(42 reference statements)
0
10
0
1
Order By: Relevance
“…[ 12 ] One case report recently mentioned the development of delayed onset subdural hematoma following epidural catheter breakage after 18 years of its placement. [ 13 ] It is clear that all patients with broken epidural catheter should be closely followed up; surgical management is required for the symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] One case report recently mentioned the development of delayed onset subdural hematoma following epidural catheter breakage after 18 years of its placement. [ 13 ] It is clear that all patients with broken epidural catheter should be closely followed up; surgical management is required for the symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ishikawa et al reported a case of delayed onset of subdural hematoma (18 years) following epidural catheter breakage, exploring the possibility of a relationship between catheter fragment and subdural hematoma. Decompression surgery was done to relieve the patient of symptoms [9]. If the proximal end of the segment is located at or just beneath the skin such that it can be retrieved through a skin incision by gentle traction [10].…”
Section: Discussionmentioning
confidence: 99%
“…The potential complications include infections and the induction of a foreign body granulomatous reaction, which could lead to symptomatic manifestations. According to available literature, most cases are reported in adult patients, including cases of long‐term retention with late clinical onset 3 . Surgical extraction is described but it is questionable 4 .…”
Section: Figurementioning
confidence: 99%